(untitled) (Journal of Economic Research & Business Administration, 2025)
The connection between overtime work and satisfaction remains a crucial yet insufficiently studied research area. This review article examines the inconsistent findings on how overtime affects job satisfaction, life satisfaction, and health-related outcomes. Its aim is to deliver a comprehensive analysis of the existing literature and highlight research gaps to inform future investigations. Key research questions are about the existing literature’s classification based on various approaches to the overtime-satisfaction relationship, overtime’s impact on job satisfaction, life satisfaction, and other related factors, and the influence of different factors on the effects of overtime on satisfaction. The article posits that overtime’s impact on satisfaction is not uniform but depends on the interaction of multiple factors, such as the amount of overtime, whether it is voluntary or mandatory, and its interference with personal life. To explore these questions, a systematic literature review was conducted, organizing studies into five key themes: recompense, overtime load, state of overtime, interference and impact. The review primarily examines cross-sectional studies across various industries. The findings indicate that a one-size-fits-all approach to managing overtime is inadequate, as the interaction of various factors is complex and context-dependent. The article concludes by advocating for a holistic approach in future research, encouraging scholars to move beyond isolated factors and adopt a multidimensional perspective. Key words: overtime, satisfaction, health, personal life, compensation.